Patterns of Parental and Peer Assistance in the Formation of Anti Bullying Behavior in Students at SMPK Citra Bangsa Mandiri Kupang - Semarlica Sarah; Ezra Tari; Yakobus Adi Saingo (Suluh: Jurnal Bimbingan dan Konseling, 2024)
The objective of this study is to identify and explain the patterns of parental and peer support in shaping anti-bullying behaviour among students at SMPK Citra Bangsa Mandiri Kupang.  Bullying is a persistent and repetitive form of aggressive behaviour characterised by an unequal power dynamic between the offender and the victim, with the intention of causing harm and exerting pressure on the victims. This study employs descriptive methodologies with a qualitative approach, utilising interview techniques. This buy is mostly aimed for the eighth grade children. The study involved a total of four participants, comprising two parents and two students. Interviews are systematically done to examine the influence of school programmes on the development of anti-bullying behaviour through observation.  The study findings indicate the existence of three distinct forms of parental support in shaping children' anti-bullying behaviour. The concept of Conscious Parenting is the deliberate and mindful approach of raising children, with a strong emphasis on attentive care and effective communication. Authoritative Parenting, the second style, is distinguished by parents who make fair requests and have high levels of responsiveness towards their children. Parents who have been given official permission not only have elevated standards for their children, but also provide them with the necessary resources and assistance to achieve success.